Toddlers track hierarchical structure dependence. (1st October 2020) - Shi, Rushen; Legrand, Camille; Brandenberger, Anna
ABSTRACT: Previous research suggests that toddlers can rely on distributional cues in the input to track adjacent and nonadjacent grammatical dependencies. It remains unclear whether toddlers understand the hierarchical phrase structures that determine the corresponding grammatical dependencies. We addressed this question by testing toddlers on two different phrase structures in French that govern distinct patterns of grammatical gender feature agreement. We first show that the two structures are in fact extremely infrequent in children's input. Then we report on a preferential looking experiment in which French-learning 30-month-olds were presented with French sentences in the two structures, and the grammaticality of the feature agreement was manipulated. Crucially, the contrasting structures contained the same sequentially ordered feature-bearing words in our design (e.g., correct agreement: La banane FEMININE dans le chapeau MASCLINE, elle FEMININE … 'The banana in the hat, it …'; incorrect agreement: *La banane FEMININE et le chapeau MASCLINE, elles FEMININE … 'The banana and the hat, they …'). Thus, children must go beyond those words and distinguish the structures hierarchically in order to determine the grammaticality of the different agreement patterns. We predicted that if toddlers rely solely on input support to acquire the structures and the agreement, they should show no discrimination of feature grammaticality. If, however, they can rely on mechanisms beyond linear input, such as the principle of structure dependence in the universal grammar (UG), they should show a grammaticality effect. The results confirmed the latter prediction, demonstrating the possible influence of the learner's internal system, suggesting that UG knowledge might guide early language development.